Electrical Neurostimulation Promotes Brown Adipose Tissue Thermogenesis - Li, Zhuang; de Jonge, Wouter J.; Wang, Yanan; Rensen, Patrick C. N.; Kooijman, Sander (Frontiers in Endocrinology, 2020)
Background: Brown adipose tissue (BAT) is present in humans and rodents, and contributes to energy expenditure by converting energy stored in lipids and glucose into heat. Beta adrenergic receptor (β-AR) agonists have been proposed as pharmacological tools to activate BAT, but they lack selectivity for this tissue. This study aimed to investigate the possibility to apply electrical neurostimulation as a novel approach to activate BAT by promoting the sympathetic outflow towards BAT. Methods: Male C57BL/6J mice were treated with either unilateral electrical neurostimulation of interscapular BAT or with the β3-AR agonist CL316,243. Thermogenesis, nutrient uptake by BAT and downstream signaling of adrenergic receptors in BAT were examined. Results: Electrical neurostimulation and β3-AR agonism acutely increased heat production by BAT, as evidenced by an increase in local temperature in BAT, without influencing the core body temperature. Both treatments acutely increased tyrosine hydroxylase content in the nerve terminals thereby confirming enhanced sympathetic activity. In addition, we identified increased phosphorylation of hormone-sensitive lipase coinciding with reduced intracellular lipids in BAT, without affecting acute nutrient uptake from plasma. The increased BAT temperature as induced by electrical neurostimulation was reversed by β3-AR antagonism. Conclusion: Electrical neurostimulation acutely promotes thermogenesis in BAT as dependent on β3-AR signaling. We anticipate that electrical neurostimulation may be further developed as a novel strategy to activate BAT and thereby combat (cardio)metabolic diseases.